Pengaruh Literasi Teknologi dan Dukungan Manajemen Terhadap Optimalisasi Pemanfaatan Sistem Keuangan Desa: Studi Empiris pada Kabupaten Musi Rawas, Sumatera Selatan - Wulandari, Chatarina Putri; Halimatusyadiah, Halimatusyadiah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to examine the influence of technology literacy and management support on the optimization of the Village Financial System (Siskeudes) utilization in Musi Rawas Regency, South Sumatra. The study employs a quantitative method with a sample of 63 villages selected through purposive sampling. Data were obtained by distributing questionnaires to village treasurers and analyzed using multiple linear regression. The results indicate that technology literacy and management support have a positive effect on the optimization of Siskeudes utilization. Adequate technology literacy enables village officials to operate system features effectively, while management support—in the form of policies and the provision of infrastructure facilities—serves as a key driver for the success of the Siskeudes system. These findings underscore that the synergy between technology literacy and management support is crucial for optimizing Siskeudes utilization to ensure accurate and timely financial reporting.